School Workshop Safety Practices and Students’ Skill Acquisition in Electrical Installation Works in Technical Colleges in Akwa Ibom State - Michael, Ofonmbuk Isaac; Udoudo, Ekereobong Sunday (Richtmann Publishing, 2012)
The study was designed to determine the relationship between School Workshop Safety Practices andStudents’ Skill Acquisition in Electrical Installation Works in Technical Colleges in Akwa Ibom State. Tworesearch questions and two hypotheses were formulated for the study. The population for the study was 45which comprised 27 Electrical Installation teachers and 18 Workshop assistants in the six TechnicalColleges in Akwa Ibom State. No sampling was taken as the whole population was used for the study. Aninstrument called School Workshop Safety Practices and Students’ Skill Acquisition in Electrical InstallationWorks (SWSPSSAEIW) was used to collect data. The collected data were analysed using Pearson-Product-Moment-Correlation Coefficient (PPMC). The results from the study showed that adherence to electricshock preventive measures and regular safety audits relate positively to students’ skill acquisition inElectrical Installation Works. It was recommended among others that Electrical Installation students shouldbe properly taught on how to keep maintenance record of equipment in the workshop and teachers ofelectrical installation should ensure that electrical students are well groomed on how to carry out accidentinvestigation procedures.